Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Terhadap Kepuasan Pengguna Sistem Informasi Manajemen RS “X” Kota Palopo: The Influence of System Quality, Information Quality and Service Quality on User Satisfaction of the Management Information System RS “X” Palopo City - Sari, Novita; Ervianingsih, Ervianingsih; Zahran, Izal (Jurnal Surya Medika (JSM), 2023)
The development of information systems and technology, which is currently increasing rapidly, is urgently needed by an organization, company or individual to process and obtain data or information more easily, quickly and accurately. "X" Hospital has many problems related to patient data and information, staff, schedules, medical records, queues, medicines, treatments, finances, number and effectiveness of employees and rooms, and so on. These problems include the process of entering data and searching, especially if the system does not use a computer, it will be difficult and take a long time. This type of research is quantitative where there are 3 independent variables and 1 dependent variable. The researcher conducted multiple linear regression tests to determine the effect of the independent variables on the dependent variable and found that system quality had a positive and significant effect on user satisfaction of the "X" Hospital Management Information System. This is evidenced by T count > T table. Information quality has a positive and significant effect on user satisfaction of hospital management information systems. This is evidenced by T count > T table. Service quality has a positive and significant effect on user satisfaction of the "X" Hospital management information system. This is evidenced by T count > T table. Based on the results of the above research, it can be concluded that system quality, information quality, and service quality greatly influence the satisfaction of users of the hospital management information system (SIMRS).